Perubahan Lingkungan Ekosistem Sungai Belawan terhadap Kualitas Air dan Keanekaragaman Makrozoobenthos sebagai Bioindikator - Mayang Sari Yeanny (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2010)
The sampling technique of this research was purposive random sampling with 4 stations. The results showed that there were 23 genera of macrozoobenthic, which were categorized into 3 phyla, 5 classes, 10 orders, 18 families. The highest density population index was shown by Terebralia 92,59  ind./m2 (station IV) and the lowest was by Littorinia, Natica, Telescopium, dan Oleacinar 3,70 ind/m2 (station IV). The diversity index of  macrozoobenthic was low, ranged from 0,86 to 1,85 and the evenness were high except station IV (0,40). Similarity index of stations I and II was 21,05, stations I and was III 42,85. This means that no resemblance was observed between those stations.. Stations II and III 53,33 were resemble. The pollution of diversity macrozoobenthic was mediumness, and station IV was heavyness of pollution. Macrozoobenthic as bioindicators was Planaria, physa, dan Sphaerium. Effected by quality of water such as; pH, DO, and COD